2004
DOI: 10.1159/000076155
|View full text |Cite
|
Sign up to set email alerts
|

Central Neural Circuitry in the Jellyfish <i>Aglantha</i>

Abstract: Like other hydrozoan medusae, Aglantha lacks a brain, but the two marginal nerve rings function together as a central nervous system. Twelve neuronal and two excitable epithelial conduction systems are described and their interactions summarized. Aglantha differs from most medusae in having giant axons. It can swim and contract its tentacles in two distinct ways (escape and slow). Escape responses are mediated primarily by giant axons but conventional interneurons are also involved in transmission of informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
150
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(155 citation statements)
references
References 67 publications
1
150
0
1
Order By: Relevance
“…For example, some cnidarian medusae possess an elaborate nerve ring around their central opening (manubrium) in addition to their diffuse nerve net (Mackie 2004). This nerve ring reflects a considerable degree of centralization.…”
Section: (A) What Is a Cns?mentioning
confidence: 99%
“…For example, some cnidarian medusae possess an elaborate nerve ring around their central opening (manubrium) in addition to their diffuse nerve net (Mackie 2004). This nerve ring reflects a considerable degree of centralization.…”
Section: (A) What Is a Cns?mentioning
confidence: 99%
“…This is seen in the separation of the two diffuse networks of the subumbrella of scyphomedusae -the 'giant fiber nerve net' and the 'diffuse nerve net' (see Satterlie and Eichinger, 2014). Similarly, separate motor and sensory networks are found in the nerve rings of hydromedusae (Arkett and Spencer, 1986a;Arkett and Spencer, 1986b;Mackie et al, 2003;Mackie, 2004), and in four species representing three hydrozoan orders, sensory cells were components of all FMRFamideimmunoreactive nerve nets while immunoreactivity was absent in known motor networks (Mackie et al, 1985). Further examination of the FMRFamide-immunoreactive nets of Polyorchis indicated that, in addition to inclusion of sensory cells, the networks were frequently associated with smooth muscle bands for fields, but not the striated musculature used in swimming (Grimmelikhuijzen and Spencer, 1984;Spencer, 1988), raising the possibility that the FMRFamide networks are mixed sensory-motor nets.…”
Section: Nervous System Originsmentioning
confidence: 95%
“…Similar integrative interactions occur between the largely parallel conducting systems of the inner and outer nerve rings of hydromedusae. Here, the number of distinct conducting systems can be considerable, as shown in the hydromedusa Aglantha digitale (Mackie, 2004).…”
Section: Nervous System Originsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these circuits, motoneurons form a network connected by gap junctions, allowing the spread of currents to large motor areas. These networks are controlled by fast giant axons, such as in the hydrozoan Aglantha [67], that receive input from mechanosensory cells.…”
Section: The Evolution Of Circuits For Muscle Contractionmentioning
confidence: 99%